PORTOFOLIO INVESTASI SEBAGAI ALTERNATIF KEPUTUSAN DI PASAR MODAL (Studi Penelitian pada Saham Bursa Efek Indonesia 2012 - Sipahutar, Robinson (UNIKA Santo Thomas, 2019)
Portfolio Analysis is one of the alternative alternative tools in making investment decisions in stocks. In investing, if it only depends on one type of stock, it is likely that many investors will bear the risk. This stage involves identifying which securities will be chosen to form a portfolio and what proportion of funds will be invested in each of these securities. The selection of these securities (in other words, investors diversify) is intended to minimize the risk borne. The selection of these securities will be influenced by risk preferences, cash needs patterns, and tax status. Investment decisions are decisions taken by investors to allocate the funds they have in the form of certain assets (financial assets) in the hope that they will get economic benefits in the future. If the decision taken is to buy a certain number of shares, then that is expected to get dividends and capital gains if the shares are resold. The main consideration for fund owners (investors) in optimizing investment decisions is to maximize the level of return on investment (risk) for certain investments (Saragih et al., 2006). The making of an investment decision framework largely determines the success of an investor in optimizing the level of investment returns and reducing as little as possible the risks faced (Markowitz, 1952). In connection with the above, the main problem in this study is how to design an optimal portfolio simulation which is a combination of LQ 45 liquid stocks listed on the Indonesia Stock Exchange (IDX). The research data was conducted on LQ 45 shares during the period March - June 2012. The variables of this study were stock prices, returns, standard deviations of returns. The statistical method used is the F-test for homogeneity of variants. The results showed that only 16 stocks had optimal portfolios. Optimal portfolio, characterized by high return and low risk.